(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: In the past, injuries were commonly seen as arbitrary and inevitable “accidents”. Nonetheless, over the recent decades, a more profound comprehension of the essence of injuries has shifted these outdated perspectives. Nowadays, both accidental and deliberate injuries are predominantly perceived as events that can be prevented with the right measures. Aim of the study: To study epidemiology of Injury Patterns at a Tertiary Care Hospital in Kashmir Valley. Material and Methods: It was a Prospective Cross-Sectional study conducted at SMHS and associated hospitals from 7th July 2022 to 20th march 2024.A total of 300 participate took part in the study. Results: In our study, the mean age of participants was 35.2 years.Among the study participants, 168 (56%) reported experiencing injuries at home while as 102 (34%) participants reported of experiencing injuries on roads.In our study, the most common site of injury among participants was lower limb (36.6%) followed by head (26.3%) and upper limb (14%).Approximately 67% of the patients were managed by surgical intervention whereas the remaining 33% were managed conservatively. Conclusion: This study highlights the importance of understanding injury patterns in a tertiary care setting. Our findings support the need for targeted prevention, better resource allocation, and improved treatment protocols, offering valuable insights for public health and clinical practice.